2023
DOI: 10.3390/toxics11090747
|View full text |Cite
|
Sign up to set email alerts
|

Sources, Degradation, Ingestion and Effects of Microplastics on Humans: A Review

Yan-Duan Lin,
Ping-Hsiu Huang,
Yu-Wei Chen
et al.

Abstract: Celluloid, the predecessor to plastic, was synthesized in 1869, and due to technological advancements, plastic products appear to be ubiquitous in daily life. The massive production, rampant usage, and inadequate disposal of plastic products have led to severe environmental pollution. Consequently, reducing the employment of plastic has emerged as a pressing concern for governments globally. This review explores microplastics, including their origins, absorption, and harmful effects on the environment and huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 339 publications
0
4
0
Order By: Relevance
“… 39 No significant differences were found in the investigated lifestyle habits involving the use of plastic products between participants with and without MPs detected in their thrombi. Considering that MPs have been detected in various foods, including salts, beer, daily drinking water, fishery products, and crop plants, 40 , 41 , 42 , 43 , 44 and that they can be released from daily necessities such as toothbrushes, 45 the sources of particle exposure for our participants may vary. It would be helpful to identify the exposure sources in future studies with larger sample sizes and thorough investigations into daily aspects involving the consumption or use of MP-contaminated products.…”
Section: Discussionmentioning
confidence: 99%
“… 39 No significant differences were found in the investigated lifestyle habits involving the use of plastic products between participants with and without MPs detected in their thrombi. Considering that MPs have been detected in various foods, including salts, beer, daily drinking water, fishery products, and crop plants, 40 , 41 , 42 , 43 , 44 and that they can be released from daily necessities such as toothbrushes, 45 the sources of particle exposure for our participants may vary. It would be helpful to identify the exposure sources in future studies with larger sample sizes and thorough investigations into daily aspects involving the consumption or use of MP-contaminated products.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that when white blood cells in the human body swallow a certain amount of microplastics, they will die, releasing enzymes and causing inflammation. This then attacks more white blood cells, triggering continuous activation and leading to a variety of inflammatory and respiratory illnesses [38]. Therefore, a series of policies on microplastic control have been issued by various countries, such as the 2019 United Nations (UN) report, "Single-Use Plastics and Microplastic Legal Restrictions", "The Toxic Substances Control Act" of 2020, and "The New Pollutants Management Action Program" enacted by China in 2021, which provide direction and support for microplastic pollution management.…”
Section: The Status Of Microplastic Biodegradation Researchmentioning
confidence: 99%
“…4–6 Drifting plastics were reported accidental entanglements for marine animals, and caused the miss ingestion such as macro to micro/nano-particles for marine biota of whale to plankton has been reported. 7–10…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Driing plastics were reported accidental entanglements for marine animals, and caused the miss ingestion such as macro to micro/nano-particles for marine biota of whale to plankton has been reported. [7][8][9][10] Since the late 1980s, BPA contaminations have been detected in rivers, lakes and oceans. 11-14 BPA [2,2-bis(4hydroxyphenyl)propane] is material for PC and EPX, commercial production started in 1957 USA.…”
Section: Introductionmentioning
confidence: 99%